Trade, Poverty, Development : Getting Beyond the WTO's Doha Deadlock. - Wilkinson, Rorden (Global institutions series., 2012)
This work seeks to look beyond the seemingly endless deadlock in the WTO's Doha round of trade negotiations that began in November 2001 and were first scheduled to conclude by January 1, 2005. As well as offering an incisive analysis of the ills of the round, with particular attention directed at the poorest and least developed countries, the book expands on how the round could be moved forward elaborating on the Statement on the Doha Development Agenda that was negotiated in Johannesburg .The work as a whole provides the reader with a critical analysis of the implications of the negotiations.